Efficacy of misoprostol over Foley’s catheter as a cervical ripening agent: a comparative study - Nimbalkar, Pankajkumar B.; Patel, Jaldhara N.; Thakor, Nilesh (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Timely induction of labour could reduce maternal mortality and morbidity as well as assure a delivery of healthy baby. Objective of present study was to evaluate the efficacy of Misoprostol as a cervical ripening agent and its comparison with Foley’s catheter in terms of success rate, safety, side effects and patient compliance. Methods: A total of 250 pregnant women requiring induction of labor were recruited. Out of 250 cases, 150 were induced with 50 microgram Misoprostol and in 100 cases Foley catheter 18 F, was placed through the internal os of the cervix during September 2014 to August 2017 at the department of Obstetrics and Gynecology, GMERS Medical College, Dharpur-Patan. Written and informed consent was taken from the patients. Outcome measures, such as change in Bishop’s score, need of augmentation, induction delivery interval; complications like hyperstimulation, fever and meconium passage were compared between two groups. Statistical analysis was performed by Epi Info 7. Results: Age range of the patients was 21 to 35 years. 72.4 % of the patients were in 21-25 years age groups. 54.4% patients were multigravida. 59.2% patients had more than 37 weeks of pregnancy. 46.4% of the patients had premature rupture of membrane as indication of labour. The mean Bishop’s score for induction was 3.21 in Misoprostol group. 81.3% patients in Misoprostol group and 88% of patients in Foley’s catheter group were delivered by vaginal delivery. 60 % patients delivered within 6 hours in Misoprostol group. (Misoprostol: 60%, Foley’s catheter: 9%, p<0.001) Incidence of thin meconium was 11.3% in Misoprostol group, 9 % in Foley’s catheter group. In Misoprostol group 3.3 women had fever after induction while it was 6% in Foley’s catheter group. Conclusions: The results of the present study confirm that vaginal misoprostol is more effective than Foleys catheter in pre-induction cervical ripening.